Skin regeneration-related mechanisms of Calcium Hydroxylapatite (CaHA): a systematic review - Amiri, Mojgan; Meçani, Renald; Niehot, Christa D.; Phillips, Terri; Kolb, Janina; Daughtry, Hua; Muka, Taulant (Frontiers in Medicine, 2023)
Introduction Calcium Hydroxylapatite (CaHA) is a common dermal filler used in aesthetic medicine for volumizing and contouring. Understanding mechanisms of actions of CaHA can help improve our understanding of its clinical applications. Methods We performed a systematic review to summarize the skin-regeneration related mechanisms of CaHA. Five bibliographic databases were searched for English-language publications that evaluated CaHA in skin regeneration outcomes including neocollagenesis, cell proliferation and growth factors, angiogenesis, vascular dynamic and inflammatory markers, among others. Methodological rigor of included studies was assessed. Results Of 2,935 identified citations, 12 studies were included for final analysis. Collagen production was reported by nine studies, cell proliferation by four, elastic fibers and/or elastin by four, and three studies on angiogenesis, while limited studies were available on the other outcomes. Six were clinical/observational studies. Only seven studies had a control group. Overall, studies showed CaHA resulted in increased cell proliferation, increased collagen production and angiogenesis, as well as in higher elastic fiber and elastin formation. Limited and inconclusive evidence was available on the other mechanisms. The majority of the studies had methodological limitations. Discussion Current evidence is limited but indicates several mechanisms through which CaHA could lead to skin regeneration, volume enhancement, and contouring. Systematic review registration https://doi.org/10.17605/OSF.IO/WY49V.